Correlation between the concentrations of lactoferrin and neutrophil gelatinase-associated lipocalin in meconium - Lisowska-Myjak, Barbara (Biometals, 2017)
Neutrophil gelatinase-associated lipocalin (NGAL) and lactoferrin (Lf) are among the key components of the innate immune system due to their ability to bind iron with high affinity and thus control inflammation. The aim of this study was to test the use of NGAL and LF measurements in meconium for the assessment of the intrauterine homeostasis. NGAL and Lf concentrations were measured using ELISA kits in all serial meconium portions (n = 81) collected from 20 healthy neonates. Mean ± SD meconium concentration of Lf was 45.07 ± 78.53 µg/g and more than 1000-fold higher compared with that of NGAL at 1.93 ± 2.46 ng/g. The correlation between the two proteins (r = 0.83, p < 0.0001) was found only for portions with Lf concentrations > 25 μg/g. High variability of NGAL and Lf concentrations in meconium and their correlations prove their key role as biomarkers of the fetal condition in utero. NGAL and Lf measured in meconium are candidate biomarkers for fetal iron status.